GWAS replication study confirms the association of PDE3A–SLCO1C1 with anti-TNF therapy response in rheumatoid arthritis. (May 2013) - Acosta-Colman, Isabel; Palau, Núria; Tornero, Jesús; Fernández-Nebro, Antonio; Blanco, Francisco; González-Alvaro, Isidoro; Cañete, Juan D; Maymó, Joan; Ballina, Javier; Fernández-Gutiérrez, Benjamín; Olivé, Alex; Corominas, Héctor; et al.
Aim: The present study was undertaken to replicate the association of candidate genes for anti-TNF response in rheumatoid arthritis. Candidate genes were selected from a recent genome-wide association study on anti-TNF response performed in a population from Denmark.Materials & methods: Genomic DNA was obtained from 315 Spanish rheumatoid arthritis patients having received an anti-TNF agent as their first biological therapy. SNPs from NR2FR2, MAP2K6, CBLN2 and PDE3A–SLCO1C1 candidate loci were genotyped.Results: The PDE3A–SLCO1C1 locus rs3794271 SNP showed a highly significant association with anti-TNF treatment response (p = 1.74 × 10 -5 ). Combining the statistical evidence from the Spanish and Danish rheumatoid arthritis cohorts, the associated rs3794271 SNP reached a genome-wide significance level of association (p = 3.3 × 10 -10 ).Conclusion: The present findings establish the PDE3A–SLCO1C1 locus as a strong genetic marker of anti-TNF therapy response. Original submitted 9 January 2013; Revision submitted 13 March 2013